1987
DOI: 10.1152/ajprenal.1987.253.2.f234
|View full text |Cite
|
Sign up to set email alerts
|

Effects of renal perfusion pressure on the natriuresis induced by atrial natriuretic factor

Abstract: Synthetic atrial natriuretic factor (ANF 101-126) was infused at 1, 5, 25, and 125 pmol X kg-1 X min-1 into the renal artery of anesthetized, one-kidney dogs. During administration of 25 and 125 pmol X kg-1 X min-1 of ANF 101-126, fractional sodium excretion (FENa) rose from 1.4 +/- 0.3 to 6.6 +/- 1.1 and 5.6 +/- 1.3% when renal perfusion pressure (RPP) was at its basal level (112 +/- 5 mmHg). When base-line RPP was lowered to 101 +/- 5 mmHg by tightening a suprarenal aortic constriction, the same doses raised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1988
1988
1994
1994

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…It has been reported that ANF is released in response to volume distention of the extracellular space (1 9). ANF acts on the glomerular membranes to oppose angiotensin 11, to directly increase permeability resulting in the glomerulotubular balance toward natriuresis, or to modulate the prevailing levels of renal perfusion pressure and renal vascular resistance (10,20,21). Recently, Manning et al…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that ANF is released in response to volume distention of the extracellular space (1 9). ANF acts on the glomerular membranes to oppose angiotensin 11, to directly increase permeability resulting in the glomerulotubular balance toward natriuresis, or to modulate the prevailing levels of renal perfusion pressure and renal vascular resistance (10,20,21). Recently, Manning et al…”
Section: Resultsmentioning
confidence: 99%
“…These effects are consistent with potentiation of the effect of endogenous ANF on the kidney and are impressive, given the fact that blood pressure most likely was reduced in these rats and the natriuretic response to ANF is dependent on an adequate renal arterial perfusion pressure. 25 Others have reported significant diuresis with the NEP inhibitors phosphoramidon and UK 69S78. 26 .…”
Section: Discussionmentioning
confidence: 99%
“…19 The modulating role of renal perfusion pressure on the natriuresis induced by ANP has also been demonstrated in experimental studies. For example, Seymour et al 20 showed that stepped reductions in renal perfusion pressure resulted in a progressive fall in the fractional excretion of sodium during ANP administration. It is suggested that a higher renal perfusion pressure in hypertensive patients is required to maintain sodium balance 7 ' 16 and may account for the failure to find elevated plasma ANP levels in uncomplicated hypertension.…”
mentioning
confidence: 99%